Enhanced vertical ordering of block copolymer films by tuning molecular mass1. Issue 41 (7th May 2015) - Zhang, Xiaohua; Douglas, Jack F.; Satija, Sushil; Karim, Alamgir
<x xml:space="preserve">Abstract</x> An orientation transition with increasing BCP molecular mass from a parallel to a perpendicular orientation.